Kinetic Energy of Emerging Neutrons Produced by Photodisintegration in a Medical Linear Accelerator - Reyes., U.; Sosa., M.; Bernal., J.; Córdova., T.; Mesa., F. (Revista Mexicana de Ingenieria Biomedica, 2013)
When a gamma photon interacts with a target nucleus a nuclear reaction can be generated, producing as a consequence the expulsion of particles from the atomic nucleus, this process is called photodisintegration. For this work, are of interest nuclear reactions of photodisintegration in which neutrons are ejected due to the interaction of photons with atomic nuclei of different materials in a linear accelerator for medical use. In this paper, the kinetic energy of photoneutrons produced by interactions with atomic nuclei of 184W, 63Cu, 27Al and 12C, which are some of the materials that constitute the head of a medical linear accelerator, is calculated. Also, the nuclei present in the construction materials of the room and the maze of the accelerator, such as, 23Na, 40Ca, and 28Si, as also in the human body, 2H, 14N and 16O, are considered. It derives an exact theoretical expression, which has a linear dependence of the energy of the produced neutrons relative to the incident photon energy. It is found that, in the majority of cases, just photons with energies above 10 MV contribute to the production of neutrons. The values calculated from the expression obtained in this work are in good agreement with those reported in the literature, that are obtained by other approaches.